THE ROLE OF THE GAMES IN TEACHING ENGLISH LANGUAGE - Шукурова, Феруза (АКТУАЛЬНОЕ В ФИЛОЛОГИИ, 2021)
This article discusses the importance of using games in teaching English. Games make classes interesting and exciting. They help improve the vocabulary of the language of students. Also games develop memory, agility, resourcefulness. The article substantiates the role of games in teaching English. Teaching lessons through activities requires convenient storage and easy retrieval of materials, objects, pictures, toys, games, conversation pieces and other props. The article provides several examples of games for use in English lessons. Using these interactive methods in English lessons more useful and meaningful. If you use active games aimed at developing students' thinking in the lessons, then you can achieve the goal set in the lesson.